Risk of tuberculosis reactivation with rituximab therapy - Alkadi, Amjad; Alduaiji, Najla; Alrehaily, Ali (International Journal of Health Sciences, 2017)
Background: Tuberculosis (TB) is one of the world’s deadliest diseases, and one-third of the world’s population is infected with it. The link between antitumor necrosis factor therapy and reactivation of latent TB is well recognized. However, only limited studies have evaluated the risk of TB with rituximab, a B-cell-targeting therapeutic agent used recently for rheumatological diseases, primarily rheumatoid arthritis. Moreover, no studies have assessed this risk in TB endemic regions with a high incidence and prevalence of TB (e.g., Saudi Arabia). Objective: To examine the risk of acquiring TB or activating latent TB in adult patients with rheumatological disease who received rituximab therapy. Methodology: Retrospective cohort study included 60 patients at King Faisal Specialist Hospital and Research Centre, Saudi Arabia, between October 1, 2010, and March 31, 2011. Result: Six patients (10%) were subsequently excluded because of the treatment for latent TB (5 patients) or prior treatment for TB (1 patient). The follow-up period was 6 months for 53 patients (98.15%) and 3 months for 1 patient (1.85%). During follow-up, none of the patients received the purified protein derivative skin test while radiological studies were performed for 30 patients (55.55%). 53 patients (98.15%) had no symptoms suggestive of TB upon follow-up, and no patient experienced a TB flare-up. Conclusion: Rituximab can be considered a first line of therapy for the management of rheumatological diseases in the presence of the risk of TB reactivation, especially in endemic areas with a high prevalence and incidence of TB.